2022
DOI: 10.1001/jamadermatol.2022.2815
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Perceived Usefulness of Patient-Submitted Store-and-Forward Teledermatology Images

Abstract: ImportancePatient-submitted images vary considerably in quality and usefulness. Studies that characterize patient-submitted images in a real-life setting are lacking.ObjectiveTo evaluate the quality and perceived usefulness of patient-submitted images as determined by dermatologists and characterize agreement of their responses.Design, Setting, and ParticipantsThis survey study included patient images submitted to the Department of Dermatology at Duke University (Durham, North Carolina) between August 1, 2018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…3 Moreover, the influx of low quality images can lead to increased physician time and burnout. 5,15 In a retrospective assessment of 1700 images of skin disease from 650 patients who had Stanford Healthcare telemedicine visits from March 2020 to June 2021, we found that 37.6% of images did not meet the quality threshold for making a clinical assessment. This finding is in line with a 2022 study 5 in which dermatologists assessed 1200 telemedicine-submitted images and found that 37.8% were of insufficient quality.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…3 Moreover, the influx of low quality images can lead to increased physician time and burnout. 5,15 In a retrospective assessment of 1700 images of skin disease from 650 patients who had Stanford Healthcare telemedicine visits from March 2020 to June 2021, we found that 37.6% of images did not meet the quality threshold for making a clinical assessment. This finding is in line with a 2022 study 5 in which dermatologists assessed 1200 telemedicine-submitted images and found that 37.8% were of insufficient quality.…”
Section: Discussionmentioning
confidence: 97%
“…In a retrospective assessment of 1700 images of skin disease from 650 patients who had Stanford Healthcare telemedicine visits from March 2020 to June 2021, we found that 37.6% of images did not meet the quality threshold for making a clinical assessment. This finding is in line with a 2022 study in which dermatologists assessed 1200 telemedicine-submitted images and found that 37.8% were of insufficient quality. In the present study, we found the most common reasons for insufficient quality were blurry images or poor lighting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Strategies adopted during COVID-19 pandemic such as email, phone or video calls and Whatsapp and Facebook supporting groups showed to be effective and safe for the management of several dermatologic conditions, with a high grade of satisfaction in patients. [6][7][8] We disagree with Falotico et al 2 who suggested in-person visits only for new patients, subjects with severe or unstable disease, or those needing diagnostic testing and procedures. Indeed, teledermatology cannot replace face-to-face consultations as the physician-patient relationship is at the basis of the daily clinical practice.…”
mentioning
confidence: 79%